Comparison of Outcomes of End-to-End versus End-to-Side Anastomoses in Lower Extremity Free Flap Reconstructions - Broer, Peter Niclas; Moellhoff, Nicholas; Mayer, Julius M.; Heidekrueger, Paul I.; Ninkovic, Milomir; Ehrl, Denis (Journal of Reconstructive Microsurgery, 2020)
Background Whether to perform an end-to-end (ETE) versus end-to-side (ETS) arterial anastomosis is an integral part of preoperative planning and intraoperative decision making in free flap-based reconstructions. This study evaluated the impact of microsurgical anastomotic technique on outcomes of lower extremity reconstructions, with a focus on patients with peripheral arterial disease (PAD).Methods Over a 6-year period, 425 patients underwent 437 microvascular lower extremity free flap reconstructions with fasciocutaneous anterolateral thigh- or gracilis muscle flaps at a single surgical center. The cases were divided into an ETE (n = 297 patients) versus ETS (n = 128 patients) group according to the anastomotic technique. A retrospective analysis of patients' demographics, perioperative details, surgical complications, free flap types, recipient sites, flap survival, and the potential impact of PAD on outcomes was performed. Patient groups were comparable regarding comorbidities, American Society of Anesthesiologists scores, types of performed free flaps and recipient sites.Results We found no significant differences between the ETE versus ETS groups regarding the rate of major or minor complications (p > 0.05). Specifically, in patients suffering from PAD (n = 64) the type of arterial anastomosis had no effect on the outcome.Conclusion Overall, no significant differences in outcomes were observed when comparing the types of performed arterial anastomosis. This observation also held true for the subgroup of patients with PAD. Given that an ETS anastomosis did not increase the risk to encounter complications while preserving distal perfusion, we believe that this technique is the method of choice, especially in patients with impaired vascular status.
Keywords: end-to-end anastomoses; end-to-side anastomoses; peripheral arterial disease